Biopreservation of Shrimps Using Composed Edible Coatings from Chitosan Nanoparticles and Cloves Extract - Ahmed A. Tayel; Aml F. Elzahy; Shaaban H. Moussa; Mohammed S. Al-Saggaf; Amany M. Diab (Journal of Food Quality)
Shrimps are highly valuable and perishable foodstuff that could be rapidly spoiled. Chitosan (Cht) was extracted and transformed into nanoparticles (NPs) via ionic gelation and fortified with cloves (Syzygium aromaticum) buds extract (CLE) for usage as antimicrobial composites against food-borne bacterial pathogens (Escherichia coli, Salmonella typhimurium, and Staphylococcus aureus) and as edible coating (EC) for shrimp (Fenneropenaeus indicus) biopreservation throughout refrigerated storage. The synthesized CLE/Cht-NPs were electrostatically cross-linked and appeared with spherical shapes and homogenized distribution, with 159.4 nm mean size diameter and positive charge of 17.4 mV. The entire agents (Cht-NPs, CLE, and CLE/Cht-NPs) exhibited remarkable antibacterial activities toward all food-borne pathogens; CLE/Cht-NPs were significantly the most forceful. The scanning micrographs of treated S. typhimurium with CLE/Cht-NPs displayed NPs ability to attach and destroy bacterial cells. The ECs-treated shrimps exhibited sharp decrease in microbial groups load (aerobic microorganisms, E. coli, Enterobacteriaceae, and staphylococci) during refrigerated storage (4 ± 1°C) for 10 days. Additionally, the sensorial attributes (appearance, odor, color, and texture) of EC-treated samples preserved their elevated qualities for storage duration. The most effective EC blend contained 1.5% from Cht/NPs and 1.0% from CLE. The CLE/Cht-NPs could be impressively recommended as effectual natural composites for shrimps’ biopreservation during cold storage.